2016
DOI: 10.1186/s40608-016-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of overweight or obesity among ever-married adult women in Bangladesh

Abstract: BackgroundThe prevalence of overweight and obesity is increasing in Bangladesh. It is higher among Bangladeshi women than among men. This study was conducted to assess a host of demographic and socioeconomic correlates of overweight and obesity, separately for the urban and rural women of Bangladesh.MethodsWe used data from the Bangladesh Demographic and Health Survey (BDHS) 2011. The BDHS provides cross-sectional data on a wide range of indicators relating to population, health, and nutrition. We analyzed nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
47
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 20 publications
30
47
2
1
Order By: Relevance
“…Our study is also a nationally representative survey that included similar population and we used the same cut offs. Another study from Bangladesh that included women of age 18 to 49 years reported prevalence of overweight (BMI ≥ 25) 18.0% using cut-points of 25, which is very similar to our results [26]. A recent study from South India in adult population of >19 years of age reported prevalence of underweight 22.7% and prevalence of overweight/obese (BMI ≥ 23) 37.0% [27].…”
Section: Discussionsupporting
confidence: 89%
“…Our study is also a nationally representative survey that included similar population and we used the same cut offs. Another study from Bangladesh that included women of age 18 to 49 years reported prevalence of overweight (BMI ≥ 25) 18.0% using cut-points of 25, which is very similar to our results [26]. A recent study from South India in adult population of >19 years of age reported prevalence of underweight 22.7% and prevalence of overweight/obese (BMI ≥ 23) 37.0% [27].…”
Section: Discussionsupporting
confidence: 89%
“…The overweight/obesity prevalence in women was as high as 39.2%, which could be attributed to the sedentary lifestyle of urban women. 25 Overweight/obesity and underweight were equally prevalent in men, reflecting their socioeconomic situation: many men still had to be involved in hard physical labour, 26 while some men could afford to eat well. Our findings suggested that both overweight/obesity and underweight should be addressed simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…As like as other developing country, Bangladesh is experiencing a rapid demographic and epidemiological transition [ 8 – 10 ]which has been associated with increases in overweight and obesity. In 2011, cross-sectional data indicated that the overall prevalence of overweight and obesity combined in women who had been or were married was 18%[ 11 ], approximately 1.5 times that reported in women aged 20 to 49 years of age in 2007[ 12 ]. However, making a direct comparison in prevalence between years is difficult due to the different age of women in each study; that is ever-married women compared to women age 20–49 years.…”
Section: Introductionmentioning
confidence: 99%